Spiciferone analogs from an endophytic fungus Phoma betae collected from desert plants in West China. (June 2018) - Tan, Xiang-Mei; Li, Lu-Ying; Sun, Li-Yan; Sun, Bing-Da; Niu, Shu-Bin; Wang, Meng-Hua; Zhang, Xiao-Yan; Sun, Wen-Song; Zhang, Gui-Shan; Deng, Hui; Xing, Xiao-Ke; Zou, Zhong-Mei; et al.
Abstract Endophytic fungi from desert, arid, and grassland areas are an ecologically important but unique group with poor chemical investigation. During our ongoing study to mine bioactive secondary metabolites from unique fungal environments, a new shunt product spiciferone F (1 ) including two new analogs spiciferones G (2 ) and H (3 ) together with four known ones spiciferone A (4 ), spiciferol A (5 ), 6, and7 were isolated from endophytic fungusPhoma betae inhabiting in plantKalidium foliatum (Pall.) Moq from Ningxia Province of West China. The planar, relative, and absolute configurations of these new compounds were elucidated by nuclear magnetic resonance, high-resolution electrospray ionization mass spectrometry, and electronic circular dichroism experiments. According to the shunt products, intermediates and analogs isolated from this endophytic fungus, the possible biosynthetic pathway of spiciferones was reconstructed. Compounds1 –7 were evaluated cytotoxic activities against three cancer cell lines HCT 116, HeLa, and MCF7, and only did1 display strong biological effect against MCF7 with a half-maximal inhibitory concentration value at 7.73 ± 0.11 μ M compared with thecis -platinum (14.32 ± 1.01 μ M).